Dukungan dan Hambatan Pembelajaran Akidah Akhlak dalam Pembentukan Karakter Peserta Didik MTs Negeri 2 Makassar: Support and Obstacles to Learning Aqidah Akhlak in Developing Students' Character at MTs Negeri 2 Makassar - Sinar, Sinar (Dirasat Islamiah: Jurnal Kajian Keislaman, 2023)
This study explores the supporting and inhibiting factors of learning aqidah akhlak in building the character of students at MTs Negeri 2 Makassar. The focus of this study is to understand the process of learning aqidah akhlak, as well as the supporting and inhibiting factors for the success of character building of students. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The results of the analysis show that the process of learning aqidah akhlak is in accordance with the applicable curriculum, students are able to practice greetings and recite the asma' al-husna. The religious character of students is influenced by factors such as family, school environment, and society. The implications of this study include the importance of religious and moral education in shaping the character of the younger generation, as well as the need for collaboration between various parties to support the learning and character building of students. These findings can be a reference for the development of character education programs at MTs Negeri 2 Makassar and also a reference for further research in the same context.